Chemical and organoleptic properties of ketapang leaf herbal tea (Terminalia catappa) with variations of the addition of mint leaf powder (Mentha piperita L.) - Sri Hartati; Sekar Kusumawati; Agustina Intan Niken Tari; Retno Widyastuti (Jurnal Riset Industri Hasil Hutan, 2022)
Herbal teas come from other than tea plant (Camelia sinensis). Among the plants that can be used to make tea are ketapang leaves. Efforts are needed to combine with other leaves to make the product more acceptable to consumers. The study aimed to determine the chemical and organoleptic properties of ketapang herbal leaf tea varied by adding mint leaf powder. The stages of the research included making ketapang leaf powder, mixing the ingredients according to the treatment, and testing the tea powder. Tests consist of testing chemical properties (moisture content, ash content, total phenolic, and antioxidant activity) and organoleptic properties (color, taste, and aroma). A completely randomized design (CRD) unidirectional pattern was used in this experiment. The treatment variable was the addition of mint leaf powder with a concentration of 0%, 1%, 2%, 3%, 4%. Analysis of Variance (ANOVA) with a significance level of 0.05 was used to analyze the data obtained. Further tests with the Duncan Multi Range Test (DMRT) were carried out if significant differences were found. The results showed that the water content of ketapang leaf herbal tea powder combined with mint leaf powder was not significantly affected by variations in the added mint leaf powder. However, the ash content had a significant effect. Adding mint leaf powder also significantly affected the antioxidant activity, total phenolics, and organoleptic properties (color, taste, and aroma) of steeping ketapang leaf herbal tea. The total phenolic content and antioxidant activity decreased with the addition of mint leaf powder. The higher the concentration of mint leaf powder added to the ketapang leaf powder, the lower the antioxidant activity. However, adding mint leaf powder up to 4% could increase panelist acceptance of the taste and aroma of ketapang herbal leaf tea.